2014
DOI: 10.1007/s12639-014-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of toxoplasmosis and related risk factors among humans referred to main laboratories of Urmia city, North West of Iran, 2013

Abstract: Toxoplasmosis is mostly asymptomatic infection in immunocompetent individuals while it can cause a severe infection in human fetus during pregnancy and immunocompromised patients. This study aimed to determine the prevalence of anti-Toxoplasma IgM and IgG seropositivity and potential risk factors of the infection in humans referred to Urmia City main diagnostic laboratories, Urmia, Iran. Totally 195 blood samples were collected from the individuals referred to main diagnostic laboratories of Urmia City, 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In a study conducted by Maraghi et al in Abadan and Khoramshahr cities, from 150 patients, 40.67% and from 250 healthy people, 26% were IgG seropositive, which is similar to the results of the present study (19). In another similar study done by Ebrahimzadeh et al, in 2013, from among a total of 37 on-dialysis patients, 56% (21 cases) and from the 37 healthy people, 26% (11 cases) were positive for Toxoplasma infection (13). Additionally, in a study done by Solhjoo et al, in Jahrom in 2008, from among 44 patients, 59.10% (26 cases) and among 44 healthy people, 36.40% (16 cases) reported to be positive for anti-Toxoplasma IgG (20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study conducted by Maraghi et al in Abadan and Khoramshahr cities, from 150 patients, 40.67% and from 250 healthy people, 26% were IgG seropositive, which is similar to the results of the present study (19). In another similar study done by Ebrahimzadeh et al, in 2013, from among a total of 37 on-dialysis patients, 56% (21 cases) and from the 37 healthy people, 26% (11 cases) were positive for Toxoplasma infection (13). Additionally, in a study done by Solhjoo et al, in Jahrom in 2008, from among 44 patients, 59.10% (26 cases) and among 44 healthy people, 36.40% (16 cases) reported to be positive for anti-Toxoplasma IgG (20).…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that dialysis does not obviate this problem. Also, the reduction of phagocytic activity and reduction in the number of natural killer cells have been reported in these patients (8,(13)(14)(15) In some studies in Turkey and Egypt, it is reported that the prevalence of anti-Toxoplasma antibodies in the ondialysis patients is higher than the controls and there was a significant positive relationship between the duration of treatment with dialysis and positive cases of anti-Toxoplasma antibodies (16,17). The present study showed higher prevalence of Toxoplasma gondii infection in ondialysis patients.…”
Section: Discussionmentioning
confidence: 86%
“…Among the three principal routes of toxoplasmosis transmission, consumption of unwashed vegetables and fruits contaminated with cat feces is an important one that sometimes may lead to food-borne outbreaks [57]. The significant association of T. gondii infections with the consumption of contaminated raw vegetables is also observed in previous studies [58][59][60]. The detection of Toxoplasma gondii in contaminated vegetables and fruits is usually performed by PCR amplification [23,[61][62][63].…”
Section: Entamoeba Contaminationmentioning
confidence: 99%
“…Toxoplasmosis is transmitted via ingesting oocyst-contaminated food or water, consuming of undercooked meat containing tissue cysts, vertical infection, organ transplantation, and blood transfusion through infected donors. [1][2][3] Clinical manifestations of infection with toxoplasmosis associated with the host immune system. Toxoplasmosis in people with a complete immune system is asymptomatic, but in cancer patients undergoing chemotherapy and patients whose immune system is weakened for any reason, such as AIDS patients, transplant recipients and hemodialysis patients are more vulnerable to acute forms of toxoplasmosis such as brain damage, neurological defects, and encephalitis in the patients.…”
Section: Introductionmentioning
confidence: 99%